Association of Presence of Aspergillus Antibodies with Hemoptysis in Patients with Old Tuberculosis or Bronchiectasis but No Radiologically Visible Mycetoma - Chu, Chung-ming (American Society for Microbiology, 2004)
Old tuberculosis and bronchiectasis are the two most important causes of chronic structural changes of lungs in our locality. In the absence of radiologically visible mycetoma, the cause of hemoptysis in these two groups of patients is largely unknown. A 17-month prospective study was carried out to compare the prevalence of Aspergillus fumigatus and Aspergillus flavus antibodies in hemoptysis patients with old tuberculosis or bronchiectasis but no radiologically visible mycetoma (cases, n = 38), hemoptysis patients with other diagnosis (control group 1, n = 29), and patients with old tuberculosis or bronchiectasis but no hemoptysis (control group 2, n = 47) by a recently developed sensitive and specific A. fumigatus and A. flavus antibody assay. There were a significantly larger number of patients with antibody against A. fumigatus or A. flavus among the cases than among the patients in control groups 1 and 2 (P < 0.05 in both comparisons). Molds were not recovered from any of the patients. Among the 10 cases with Aspergillus antibody, eight and two had antibody against A. flavus and A. fumigatus, respectively. We conclude that there was an association between the presence of Aspergillus antibodies and hemoptysis in patients with old tuberculosis or bronchiectasis, suggesting that these patients probably had occult infections caused by the corresponding fungi. Development of serological tests against other Aspergillus species as well as other causes of mycetoma will probably increase the detection of occult mold infections in patients with existing parenchymal lung diseases, and treatment of fungal microinvasion may help to alleviate hemoptysis in these patients with bronchiectasis or old tuberculosis who have Aspergillus antibodies.